Development of cochleate technology towards functional design and continuous production - Shuddhodana (Nanyang Technological University, 2021)
Cochleates are supramolecular system of solid particulates comprised of large and continuous bilayer sheets of phospholipids, rolled-up to form scroll-like cylinders with little or no aqueous phase incorporated within the core. Lipid cochleates have emerged as a promising scaffold for the encapsulation of active molecules with applications in drug delivery and material science. However, research efforts focused on their formation, functional design, and reliable, controlled production, especially in a continuous fashion have remained largely unexplored and are essential for their successful translation. The design aspects of drug delivery systems are crucial for their functional outcome. Hence, the mechanism of formation, design, and its consequences on the functional properties of cochleates formed using amikacin as a non-metallic bridging agent, with and without Ca2+ in sub-threshold concentration, in comparison to conventional Ca2+-bridged cochleates were investigated. Based on the observations, a synergistic binding model involving both amikacin and Ca2+ for the bridging of phospholipid headgroups to form rigidly packed multiple bilayer cochleates was proposed. Additionally, tuneable amikacin release by simply varying the sub-threshold Ca2+ concentration with respect to amikacin was unravelled by studying the drug release kinetics. This study demonstrated the possibility of controlling the functional outcome by choosing specific type and concentration of the bridging agents used for the preparation of cochleates. A cochleate-based formulation was then developed for the effective oral delivery of artemisinin, a life-saving antimalarial drug characterized by poor bioavailability. The importance of lipid composition for the successful formation of cochleates with optimal encapsulation and loading of artemisinin was presented. A facile method for the coating of cochleates with alginate was developed to avoid their rapid dissociation under low pH gastric conditions. The alginate-coated cochleates showed better in-vitro controlled-release of artemisinin under simulated gastro-intestinal conditions than uncoated cochleates. While this study demonstrates the benefits of surface coating of cochleates with functional agents like alginate for enhanced oral delivery of artemisinin and similar drugs, it also opens attractive prospects for active targeting. In addition to effectively designing a cochleate-based system to suit controlled-delivery of encapsulated drugs, it is important to develop a novel and efficient process for the preparation of cochleates that can overcome the challenges associated with existing conventional batch processes. Hence, a continuous flow-based process for the preparation of drug-loaded cochleates was developed. An inexpensive off-the-shelf flow focusing device was used to successfully prepare artemisinin-loaded cochleates with high throughput. By carefully controlling the flow focusing parameters, cochleates of uniform and tuneable size were obtained with low dispersity, narrow size distribution, and high reproducibility as compared to the batch process. These cochleates were non-toxic and showed effective transepithelial permeability of artemisinin across intestinal Caco-2 monolayer indicating better in-vitro bioavailability. Therefore, the off-the-shelf flow focusing device is envisioned to be a highly promising platform for continuous and high-throughput production of drug-loaded cochleates in a controlled and reproducible manner. Overall, this thesis addresses several aspects such as the mechanistic understanding of cochleate formation to achieve a desired functional outcome, the effect of lipid composition on cochleate formation and drug encapsulation, their surface modification towards better controlled-release in gastro-intestinal milieu using functional coating with alginate, and a robust, reliable continuous flow-based process for their preparation. Therefore, this dissertation is believed not only to help and guide the future design of cochleates with specific functions in drug delivery and formulation, but also to potentially enable their smooth clinical translation with predictable drug release, absorption, and bioavailability.